"Management of recurrent temporomandibular dislocation using orthodontic traction screws.". Issue 11 (November 2021) - Santás Alegret, Mario; Fernández García, Antonio; Gómez, Vicenç J.; Olavarria Montes, Eduardo; Mejía Nieto, María; Sánchez Aniceto, Gregorio
Abstract: Temporomandibular joint dislocation is defined as the loss of joint congruency between the mandibular condyle and the glenoid fossa of the temporal bone. Multiple therapeutic options have been proposed for the treatment of recurrent TMJ dislocation. The aim of this paper is to present two recently treated cases with a modification of Wolford's technique, replacing the Mitek anchors with orthodontic screws. Case series : The first case concerns a 36 year-old women with recurrent temporomandibular dislocation, and the second one a 26 year-old patient with the same diagnosis. In both cases, one 8mm orthodontic screw was placed in the lateral pole of mandibular condyle, sutured with PremiCron® 2/0 to a hole made in the root of each zygomatic arch. At twelve-month follow-up (first patient) and at six-month follow-up (second patient), patients had not presented new episodes of mandibular dislocation and mouth opening range remained stable. This technique can be considered as an alternative to Wolford's technique in treating recurrent temporomandibular dislocation when conservative management fails.